PENGARUH IKLAN DAN KEPERCAYAAN MEREK TERHADAP MINAT BELI KONSUMEN (STUDI PADA TEXAS CHICKEN PEKANBARU) - Algamar Putra; Meizy Heriyanto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study aims to determine the effect of advertising and brand trust on costumer purchase interest ( A case on Texas Chicken Pekanbaru . The advertising as a variable ( X1 ) trust the brand as a variable ( X2 ) and customer purchase interest as ( Y ) .The method in this research is descriptive and quantitative using SPSS 20 , where the sample used is the consumer Texas Chicken Pekanbaru with about 100 respondent . The formula used to determine the sample slovin , as well as a sampling technique by accidental sampling . Data collection through questionnaires .Results of analysis using multiple linear regression , t test and f test so it can be known that the advertising variable positive effect on customer purchase interest , brand trust significant effect on consumer purchase interest , and significant effect between brand advertising and brand trust on customerprchase interest .Keywords : Advertising, Brand Trust an Customer Purchase Interest